THE ROLE OF THE INTERNET IN PROMOTING ENGLISH LANGUAGE LEARNING LESSONS - Kholmuhamedova N.M.; Turgunov SH. (Лучшие интеллектуальные исследования, 2024)
Abstract: For the time being social media are becoming common with an easy way of learning languages. Knowledge of promoting social skills helps to create effective teaching lesson plans. The article explores the various ways in which the Internet facilitates language learning, including access to online courses, language exchange platforms, and interactive tools. Furthermore, it examines the role of social media and online communities in providing learners with opportunities for authentic language use and cultural immersion. The internet enables learners to customize their learning experience, access authentic materials, and engage with diverse communities, ultimately enhancing their language proficiency and cultural understanding.